PIANO LESSONS FOR BRAIN HEALTH? A REVIEW OF COGNITIVE, AUDITORY, AND FUNCTIONAL OUTCOMES IN OLDER ADULTHOOD - Rosa, Katarzyna; Żurek, Paweł; Danielczyk, Daria; Pałubska, Jagoda; Muller, Oliwer; Malatyńska, Natalia; Czyżewski, Wiktor; Szymczyk, Martyna; Chudzicki, Kamil (International Journal of Innovative Technologies in Social Science, 2026)
Objective: To synthesize current evidence on whether piano or keyboard training supports brain health in older adulthood, with particular attention to executive function, central auditory processing, everyday function, and quality of life. Methodology: This narrative review was informed by PubMed/MEDLINE and PubMed Central searches updated through March 2026, complemented by backward and forward citation tracking of key randomized and controlled studies. Priority was given to intervention trials, mechanistic longitudinal analyses, systematic reviews, and protocols relevant to older adults with and without mild cognitive impairment. Results: The evidence base includes early randomized studies of beginner piano lessons, active-controlled trials comparing piano with computerized cognitive training or music-listening curricula, neuroimaging analyses nested within randomized trials, and emerging remote or robot-assisted delivery models. The clearest benefits appear in selected executive domains, especially processing speed, category switching, and some aspects of cognitive flexibility. By contrast, the largest active-controlled trial did not find superiority of piano training over music listening for auditory processing, global cognition, or everyday function. Longer interventions may be more favorable, and recent work suggests quality-of-life gains and neuroplasticity signals in white and grey matter. Conclusion: Piano lessons are a plausible, engaging, and socially meaningful multimodal activity for healthy aging, but current evidence does not justify strong claims about dementia prevention or broad everyday functional gains. Future research should clarify dose-response relationships, identify which older adults benefit most, and test scalable technology-enabled models suitable for community and home-based use.